Thinking about development - Streeten, Paul Patrick (Cambridge, 1997)
Paul Streeten is recognised as one of the profession's most eminent authorities on economic development. In these lectures he provides a major statement on his approach to the development problem, stressing that human development, not simply income growth, should be the focus of all strategies to eradicate hunger and poverty in the world. His argument assigns an important role to reformed government - both in providing social services and in facilitating the functioning of markets - in opposition to the prevailing idea that minimal government is more often than not the optimal solution. The role of small and larger firms, institutions, central and local government is also carefully examined. Streeten outlines a normative political economy - how to mobilise reformist alliances, how to use interest group, how to harness coalition - in the pursuit of effective development.
Keywords: Economic development